Repetitive eating questionnaire [Rep(eat)-Q]: enlightening the concept of grazing 2 and psychometric properties in a Portuguese sample - Conceição, Eva Martins (2017)
Background/objective: Grazing has been associated with poor weight loss or weight regain in obese patients undergoing bariatric surgery, but research remains scarce and complicated by the use of different non-validated measures. The aim of this paper is to describe the validation of the Rep(eat)-Q a self-report measure developed to assess grazing, and investigates its relationship with BMI and psychopathology.Subjects/Methods: 1223 university students and community participants (non-clinical; Study A) and 154 pre-bariatric and 84 post-bariatric patients (Study B) completed a set of self-report measures, including the Rep(eat)-Q (worded in Portuguese), to assess disordered eating, depression, anxiety, stress and impulsivity. Exploratory and confirmatory factor analyses tested the factor structure; internal consistency construct, convergent and divergent validity were also tested.Results: The Rep(eat)-Q scales showed good internal consistency (alpha >= 0.849) and temporal stability (r(sp) = 0.824, p < 0.000). Factor analyses generated two subscales: compulsive grazing and repetitive eating. Significant correlations (p < 0.05) were found between the Rep(eat)-Q and BMI in the non-clinical population and weight loss and weight regain in the bariatric sample. Generally, the correlations with psychological distress were weak (r(sp) < 0.4). Strong and significant (r(sp)>= 0.4; p's < 0.05) correlations were found between compulsive grazing and eating disorder psychopathology. Repetitive eating subscale was inversely correlated with cognitive restraint (r(sp) -0.321, p < 0.05) and directly correlated with uncontrolled eating and emotional eating (r(sp) = 0.754; r(sp) = 0.691; p < 0.05).Discussion/conclusion: The Rep(eat)-Q is a valid measure to assess grazing in non-clinical and in bariatric surgery populations. Grazing can be conceptualized on the spectrum of disordered eating behavior, and appears associated with loss of control over eating. Considering the link between grazing and weight outcomes, the Rep(eat)-Q represe